Effects of Chronic Roundup Exposure on Medaka Larvae - Deborah Killian; Mehwish Faheem; Beh Reh; Xuegeng Wang; Ramji Kumar Bhandari (MDPI AG, 2023)
The use of glyphosate-based herbicides is increasing yearly to keep up with the growing demands of the agriculture world. Although glyphosate-based herbicides target the enzymatic pathway in plants, the effects on the endocrine systems of vertebrate organisms, mainly fish, are widely unknown. Many studies with glyphosate used high-exposure concentrations (mg/L), and the effect of environmentally relevant or lower concentrations has not been clearly understood. Therefore, the present study examined the effects of very low, environmentally relevant, and high concentrations of glyphosate exposure on embryo development and the thyroid system of Japanese medaka (Oryzias latipes). The Hd-rR medaka embryos were exposed to Roundup containing 0.05, 0.5, 5, 10, and 20 mg/L glyphosate (glyphosate acid equivalent) from the 8 h post-fertilization stage through the 14-day post-fertilization stage. Phenotypes observed include delayed hatching, increased developmental deformities, abnormal growth, and embryo mortality. The lowest concentration of glyphosate (0.05 mg/L) and the highest concentration (20 mg/L) induced similar phenotypes in embryos and fry. A significant decrease in mRNA levels for acetylcholinesterase (ache) and thyroid hormone receptor alpha (thrα) was found in the fry exposed to 0.05 mg/L and 20 mg/L glyphosate. The present results demonstrated that exposure to glyphosate formulation, at a concentration of 0.05 mg/L, can affect the early development of medaka larvae and the thyroid pathway, suggesting a link between thyroid functional changes and developmental alteration; they also showed that glyphosate can be toxic to fish at this concentration.